Pengaruh Opini Audit, Financial Distress, Pergantian Manajemen terhadap Auditor Switching: - Lilik Pujiati; Liya Rizkiyah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of audit opinion, financial distress, and management changes on auditor switching. The dependent variable in this study is auditor switching, while the independent variables measured in the implementation of this research are audit opinion, financial distress, and management turnover. This type of research is quantitative research with a population obtained from BUMN companies registered on the BUMN website in 2020-2022. The sampling technique used was purposive sampling technique and produced 10 sample companies for 3 years of observation. The type of data used is secondary taken from the financial statements of state-owned companies. The analysis technique used in this study is logistic regression analysis using SPSS version 20. The results of the analysis in this study indicate that audit opinion, financial distress and management turnover have no effect on auditor switching. The coefficient of determination (R2) in this study is 7.9% while the rest is explained by variables with other models outside this study. Kata Kunci: Audit Opinion; Financial Distress; Change of Management; Switching Auditors